Program Boga Sehat Sebagai Upaya Kepedulian Terhadap Lanjut Usia di Kabupaten Bantul Program Boga Sehat Sebagai Upaya Kepedulian Terhadap Lanjut Usia di Kabupaten Bantul: Program Boga Sehat Sebagai Upaya Kepedulian Terhadap Lanjut Usia di Kabupaten Bantul - Ahmad Syahrial Semen Dawai; Risky Eka Amriyanto (Sekolah Tinggi Pembangunan Masyarakat Desa APMD, 2022)
This study aims to describe and analyze the implementation of the Healthy Catering Program (Program Boga Sehat) in general and find out the obstacles to the implementation of the Healthy Catering Program. The research method used is a descriptive study with a qualitative approach. The method of data collection in this study was through observation, interviews, and supported by secondary data in the form of supporting documents. The finding of this study is that the implementation of the Healthy Catering Program aims to provide basic fulfillment for the elderly and severe disabilities through the provision of nutritious food. This program has adjustments and complementary or supporting programs at the kapanewon and village levels to manage the program according to regional conditions and reach more elderly people and people with disabilities. The problems encountered were related to administration, the elderly who were resistant to the menu provided, and the Healthy Catering Program was still unable to reach all neglected elderly people in Bantul Regency. In addition, the Healthy Catering Program is only limited to meeting basic needs and has not been able to significantly reduce poverty in Bantul Regency.